Analisis Pengaruh Sosial Ekonomi Terhadap Tingkat Kriminalitas di Indonesia (Studi Kasus 32 Provinsi di Indonesia) - Sukmawati Liamanu; Lestari Sukarniati; Firsty Ramadhona Amalia Lubis (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2023)
In this modern era, a prevalent social issue faced by almost every country is unemployment. Increasing unemployment rates in a region can trigger criminal activities. The objective of this research is to examine the influence of socio-economic variables, namely, unemployment, poverty, education, population density, and per capita GDP in Indonesia's 32 provinces. This study employs quantitative research methods and utilizes secondary data obtained from the Central Bureau of Statistics (BPS). Data panel regression is used for data analysis. The results of this study indicate that unemployment, poverty, education, and population density do not have a significant impact. Only per capita GDP shows a coefficient of -0.539228, indicating a negative influence on the crime rate in Indonesia. However, in the case of the per capita GDP variable, the p-value is 0.0496 < 0.05, signifying that per capita GDP has a significant impact on the crime rate in Indonesia. This means that an increase in per capita GDP leads to a lower crime rate in Indonesia, as higher per capita GDP in a region contributes to economic growth and advancement.